ANALYSIS OF THE TECHNOLOGICAL SCHEME OF FIRE-RESISTANT BRICK PRODUCTION - Bobojon Ortiqaliyev; Azimjon Abdurayimov (European Science Publishing, 2023)
The article describes the Sito-burat SM-237A machine for sorting raw materials of refractory bricks, which is used in chemical industry, building materials production, and metallurgical industries in our country, and the analysis of the technological scheme of refractory brick production.
Keywords: Sito-burat SM-237A, firebrick, sorting device, granulometric composition, production, raw materials.